Influence of leadership to determine the organizational performance on the change management, culture and employee focus - Zainol Mustafa; Mohd Firdausil Afnan Razali; Rieza Zulrian Aldio; Nur Riza Mohd Suradi (Penerbit Universiti Kebangsaan Malaysia, 2020)
Leadership is one of the keys to own a successful organization and performance is commonly set as the benchmark. However, the employees also need to play their role effectively in order to achieve a high performance. Due to the world modernization, numerous value crisis occurred among employees and leaders which affect the performance of the organization. Hence, various studies had been carried out to identify implication of the values or core values in criteria. This study measures the public university performance using the Value-Based Total Performance Excellence Model (VBTPEM). Leadership criteria and employee criteria in the area of employee focus, change management and culture were analysed to observe the importance of these criteria towards university performance. Using Partial Least Square method, the relationship between all the criteria were determined in the VBTPEM model. Findings shows that values in leadership play a significant role in influencing values in Employee focus (ß = 0.565), change management (ß = 0.608) and culture (ß = 0.587) with R 2=56.9%. These indicates, change performance, culture and employee focus are very vital in shaping positive leadership, in developing an inspiring organization.